Analysis of the content of nature scientific photographs: proposal of a pattern - Doucet, Anne-Vinciane (Revista General de Información y Documentación, 2014)
This article proposes a pattern to analyse the content of scientific photographs. In a first part, it defines scientific photographs, its public and its analysis. In a second part, it deals with the importance of the text which encloses the photographs to be retrieved. In a third part, it describes the Lasswell model, the Panofsky and Shatford models, and the semiology. The method followed to analyse photographs is then detailed. In a fourth part, it stresses how useful is the pattern statistically to write an abstract and to assign keywords, before it concludes about the importance to detect the informative clues transmitted by the photographer and the necessary collaboration between photographer and information professional.
Keywords: scientific photographs; content analysis; semiology; Lasswell model; Panofsky model